2015
DOI: 10.1530/erc-15-0045
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin is an inflammatory mediator and therapeutic target in thyroid cancer

Abstract: Autotaxin is a secreted enzyme that converts extracellular lysophosphatidylcholine to lysophosphatidate (LPA). In cancers, LPA increases tumour growth, metastasis and chemoresistance by activating six G-protein coupled receptors. We examined O200 human thyroid biopsies. Autotaxin expression in metastatic deposits and primary carcinomas was four-to tenfold higher than in benign neoplasms or normal thyroid tissue. Autotaxin immunohistochemical staining was also increased in benign neoplasms with leukocytic infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 63 publications
2
53
0
Order By: Relevance
“…Recently, we showed that high expression of ATX and inflammatory mediators distinguishes thyroid tumors from benign thyroid nodules. LPA treatment of thyroid cancer cells significantly increases the production of 16 inflammatory mediators, which in turn increase ATX production by the cancer cells (65). Thyroid tumor growth in mouse xenograft models was slowed by >50% by treatment with ONO‐8430506 (65), accompanied by a significant decrease in tumor expression of 16 inflammatory mediators (65), which in cell culture increased thyroid cancer cell growth (65).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that high expression of ATX and inflammatory mediators distinguishes thyroid tumors from benign thyroid nodules. LPA treatment of thyroid cancer cells significantly increases the production of 16 inflammatory mediators, which in turn increase ATX production by the cancer cells (65). Thyroid tumor growth in mouse xenograft models was slowed by >50% by treatment with ONO‐8430506 (65), accompanied by a significant decrease in tumor expression of 16 inflammatory mediators (65), which in cell culture increased thyroid cancer cell growth (65).…”
Section: Discussionmentioning
confidence: 99%
“…It could also have been caused secondary to the decrease in LPA concentrations because LPA can increase S1P release from cells ( 42 ). However, we think that this is unlikely because decreasing plasma LPA concentrations with an ATX inhibitor did not lower the concentration of circulating S1P ( 13 ). A further possibility is that tetracyclines exert an anti-infl ammatory effect ( 43,44 ), which might indirectly decrease plasma S1P concentrations ( 45 ).…”
Section: Doxycycline Increased Lpa Clearance From the Circulation Of mentioning
confidence: 99%
“…This ATX-LPA-inflammatory axis in cancers promotes tumor growth, metastasis, and the loss of efficacy of chemotherapy and radiotherapy (6,12). The cycle can be attenuated in thyroid and breast cancer by inhibiting ATX, which decreases the production of .16 inflammatory cytokines and chemokines in the inflamed areas (13,14). Also, increasing the low LPP1 activity in breast and thyroid cancer cells decreases inflammation, tumor growth, and metastasis (15).…”
mentioning
confidence: 99%